Cyber-Physical Systems in Smart Grids Enhancing Energy Management and Distribution Efficiency - Ponnusamy Sivakumar; Gurugubelli Vanitha; G V Rambabu; Sheeba Adlin; Tiwari Mohit; T Saravanan (ITM Web of Conferences)
This paper aims to study the interaction and correlation of Cyber-Physical Systems (CPS) with emphasis on Smart Grids (SGs) to enhance and develop energy utilization and distribution systems. This study aligns with the design of adaptive, real-time operations that respond continuously and dynamically to energy demand fluctuations and can increase grid reliability and decrease operational costs through optimization. Novel solutions to some generic challenges of the grid, such as communication burdens and cyber-security threats are the application of new optimization algorithms, machine learning methods and scalable remediation measures. This work seeks to both investigate emerging technologies such as LoRa (Long Range, low power) and autonomous systems, and to lead in the development of intelligent, self-optimised smart grid infrastructures. Additionally, the dissertation addresses societal and regulatory challenges to decarbonization, guaranteeing that the solution is technically possible, as well as economically and politically possible. All of this effort will contribute to green, secure and renewable-integrated smart grids in the future.